Employing a Decision Support System (DSS) application system to modify a non-standard wall-mounting electrical panel using a 3D CAD modelling - Muhammad Arifur Rahman; Sally Cahyati (Universitas Mercu Buana, 2022)
Flexibility in the design process becomes an absolute necessity in a smart factory in the era of industrial manufacturing 4.0. CAD technology with a 3D modeling capability serves as a backbone in the design process in a manufacturing industry. Here, iLogic serving as an add-on of Inventor software will be combined with a Decision Support System (DSS) to build a DSS application system, namely